2009
DOI: 10.2176/nmc.49.213
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Artery Embolization During Carotid Angioplasty and Carotid Artery Stenting -Case Report-

Abstract: A 69-year-old man presented with a rare case of retinal artery embolization, which occurred as a complication of carotid angioplasty and carotid artery stenting performed for recurrent cerebral infarction. Magnetic resonance imaging and angiography showed right internal carotid artery stenosis with ulceration. Carotid angioplasty and carotid artery stenting were performed using the distal protection system with the PercuSurge GuardWire. However, just after dilation, the patient complained of ocular pain and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several studies reported CRAO or BRAO after CAS 8)11-13). Samardzic et al10) reported retinal circulation embolism after cardiac procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported CRAO or BRAO after CAS 8)11-13). Samardzic et al10) reported retinal circulation embolism after cardiac procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis of the ophthalmic artery can be another cause of CRAO 11). The third mechanism involves anastomosis between the ophthalmic artery and the external carotid artery 12)13). The ophthalmic artery has numerous extra-orbital branches, which can have extensive anastomoses with the ICA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinal artery occlusion (RAO) has also been known to occur in CAS, and various causes have been reported. [4][5][6][7][8][9] According to previous reports, the prevalence of all retinal artery embolisation during CAS is 5-16.9% and that of symptomatic RAO is 1.4-1.7%. 5,7,8 Thus central RAO and branch RAO are not rare complications of CAS; these are very severe complications because they are difficult to treat and result in a decline in activities of daily living caused by the irreversible visual disturbance.…”
Section: Introductionmentioning
confidence: 99%